IEG at fifty - Institute of Economic Growth (New Delhi, 2008)
Commemorating the 50th anniversary of one of the top ranked economic institutions in India, several illustrious members of present and former faculty have come forward to share their thoughts, memories, and feelings for the Institute of Economic Growth (IEG). These recollections and reflections provide an insight into the creation of the institution and its contribution to training, teaching, and policymaking. Illustrated with historical photographs and informative graphics, this commemorative volume also reflects the evolution of research in the social sciences field at IEG.
Keywords: Institute of economic growth ( India)